Imazalil and wax coating application in citrus packhouses to control green mould and preserve fruit quality - Njombolwana, Ncumisa Shelly (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--Stellenbosch University, 2012.